2013
DOI: 10.1002/chem.201300160
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Rhodium Catalyst for Z‐Selective Anti‐Markovnikov Addition of Carboxylic Acids to Terminal Alkynes

Abstract: To develop more active catalysts for the rhodium-catalyzed addition of carboxylic acids to terminal alkynes furnishing anti-Markovnikov Z enol esters, a thorough study of the rhodium complexes involved was performed. A number of rhodium complexes were characterized by NMR, ESI-MS, and X-ray analysis and applied as catalysts for the title reaction. The systematic investigations revealed that the presence of chloride ions decreased the catalyst activity. Conversely, generating and applying a mixture of two rhodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 64 publications
0
23
2
1
Order By: Relevance
“…[1][2][3] It has been shown that allenes [5,6] or dienes [7,8] provide completely atomefficient access to allylmetal intermediates.Although the stoichiometric conversion of alkynes into allenes [9] and p-allylmetal complexes [10] has been documented, the use of alkynes as allylmetal precursors is far less developed. However, the use of alkynes as precursors to both electrophilic and nucleophilic allylmetal species has witnessed enormous progress recently.Inthe context of electrophilic allylation, that is,a lkyne-mediated Tsuji-Trost reactions,c atalysts based on palladium [11][12][13][14][15] and rhodium [16][17][18][19] have been developed. Even more recently,a lkyne-mediated nucleophilic allylations of carbonyl compounds in the presence of iridium [20] or ruthenium [21] catalysts have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] It has been shown that allenes [5,6] or dienes [7,8] provide completely atomefficient access to allylmetal intermediates.Although the stoichiometric conversion of alkynes into allenes [9] and p-allylmetal complexes [10] has been documented, the use of alkynes as allylmetal precursors is far less developed. However, the use of alkynes as precursors to both electrophilic and nucleophilic allylmetal species has witnessed enormous progress recently.Inthe context of electrophilic allylation, that is,a lkyne-mediated Tsuji-Trost reactions,c atalysts based on palladium [11][12][13][14][15] and rhodium [16][17][18][19] have been developed. Even more recently,a lkyne-mediated nucleophilic allylations of carbonyl compounds in the presence of iridium [20] or ruthenium [21] catalysts have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In both electrophilic or nucleophilic modes,c ompletely atom-efficient catalytic processes are enabled, and in several cases enantioselective transformations have been achieved. [11][12][13][14][15][16][17][18][19][20][21] Many of these processes represent examples of "tandem catalysis," as asingle metal complex will catalyze the isomerization of an alkyne to an allene and, in as eparate catalytic process,t ransform the allene to ap roduct of electrophilic or nucleophilic allylation. In this Minireview,w eo ffer an exhaustive account of this emerging area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Application References pyridyl phosphines OLEDs [13] Heck coupling [14] metal organic frameworks [15] polymerization of lactides [16] alkene hydroxylation [17] addition reaction [18] ethylene oligomerization [19] synthesis of pyrazolines [20] triazolyl phosphines Suzuki cross coupling [21] asymmetric hydrogenation [22] luminescence [23] hydroformylation [24] pyrazolyl phosphines coordination polymers [25] Heck coupling [26] imidazolyl phosphines Suzuki coupling [27] hydroamination [28] OLEDs [29] ethylene oligomerization [30] amination [31] olefin metathesis [32] hydroformylation [33] pyrrolyl phosphines hydroformylation [34,35] ethylene polymerization [36] oxazolyl phosphines asymmetric cycloaddition [37] asymmetric hydrogenation [38] carbonylation of alkynes [39] allylic substitution [40] asymmetric addition [41] allylic amination [42,43] The presence of soft donor atoms such as phosphorus results in the formation of hemilabile ligands. These are multidentate ligands having hard P-donor and soft N-and/or O-donor atoms [44].…”
Section: Type Of Ligandmentioning
confidence: 99%
“…Diese verzweigte Regioselektivität, wie sie auch aus konventionellen Rhodium‐katalysierten allylischen Substitutionen und verwandten Allen‐Hydrofunktionalisierungen bekannt ist, bietet daher eine wertvolle Ergänzung zur linearen Selektivität, wie sie in Palladium‐katalysierten Allylierungen beobachtet wird. Insgesamt erwies sich die Methode als sehr empfindlich bezüglich der Wahl des Liganden: Während ein Rhodium/DPEphos‐basierter Katalysator selektiv Zugang zu den verzweigten Allylestern eröffnete, konnten unter Verwendung des P/N‐Liganden DPPMP darüber hinaus auch die entsprechenden Z ‐Enolester als Hauptprodukte erhalten werden (Schema ) ,…”
Section: Alkine Als Elektrophile π‐Allyl‐vorstufenunclassified